2015
DOI: 10.1155/2015/354957
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects Mediated by Serotonin

Abstract: Serotonin (5-HT) induces concentration-dependent metabolic effects in diverse cell types, including neurons, entherochromaffin cells, adipocytes, pancreatic beta-cells, fibroblasts, smooth muscle cells, epithelial cells, and leukocytes. Three classes of genes regulating 5-HT function are constitutively expressed or induced in these cells: (a) membrane proteins that regulate the response to 5-HT, such as SERT, 5HTR-GPCR, and the 5HT3-ion channels; (b) downstream signaling transduction proteins; and (c) enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
132
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(139 citation statements)
references
References 245 publications
(258 reference statements)
4
132
0
3
Order By: Relevance
“…[42,43] It is one of the most important neurotransmitters in the central nervous system (CNS) regulating multiple physiological functions such as body temperature, appetite, sleep, mood and pain. [44] Several studies reported that pathological change in 5-HT level have been associated with AD, anxiety and Depression. [45,46] The decrease in the level of tissue 5-HT may be attributed to amyloid depositions in the projection sites of serotonergic neurons lead to the degeneration of 5-HT axons followed by the degeneration of the corresponding neuronal cell bodies.…”
Section: Discussionmentioning
confidence: 99%
“…[42,43] It is one of the most important neurotransmitters in the central nervous system (CNS) regulating multiple physiological functions such as body temperature, appetite, sleep, mood and pain. [44] Several studies reported that pathological change in 5-HT level have been associated with AD, anxiety and Depression. [45,46] The decrease in the level of tissue 5-HT may be attributed to amyloid depositions in the projection sites of serotonergic neurons lead to the degeneration of 5-HT axons followed by the degeneration of the corresponding neuronal cell bodies.…”
Section: Discussionmentioning
confidence: 99%
“…The T102C polymorphism in HTR2A gene encoding 5-HT2A is also postulated to be a risk factor for FM [38]. As 5-HT2 and 5-HT3 are involved in pain perception, the treatment with 5-HT3 antagonist or inhibition of 5-HT reuptake is effective in FM patients [39]. The SSRI administration is necessary as depression is a common disorder among FM patients and it is present in up to 80% of individuals [34].…”
Section: Serotonin and Its Metabolites In Migrainementioning
confidence: 99%
“…The cells of the immune system possess all the components of the serotonergic system, having the necessary machinery to not only be sensitive to serotonin, but also to produce and catabolize this amine [31]. Despite of attending to "molecular prerequisites", the action of the serotonin on the modulation of the immune response is still underexplored.…”
Section: Serotonin and Leukocytesmentioning
confidence: 99%
“…Despite of attending to "molecular prerequisites", the action of the serotonin on the modulation of the immune response is still underexplored. What it's known is that it can induce to changes in the profile of the leukocyte secreted cytokines [31]. Besides, some studies suggest the existence of a complex cross-communication mechanism between the signaling triggered by 5-HT receptors and the signaling induced by molecular pattern recognition receptors [32].…”
Section: Serotonin and Leukocytesmentioning
confidence: 99%